2020
DOI: 10.46861/bmp.28.353
|View full text |Cite
|
Sign up to set email alerts
|

Minerály řady bavenit-bohseit z pegmatitu Schinderhübel I v Maršíkově (silezikum, Česká republika)

Abstract: Bavenite and bohseite were found in an archive sample from Schinderhübel I granitic pegmatite, situated ca. 50 m NE from the famous chrysoberyl-bearing pegmatite body Schinderhübel III near Maršíkov (Silesicum, Czech Republic). Minerals of the bavenite-bohseite series together with minor quartz, muscovite and albite form chalky white radial aggregates up to 3.5 cm in size within a fissure cutting the pegmatite. The electron microprobe data revealed 29.0 - 65.4 mol. % of bavenite component, 0.03 - 0.12 apfu Na … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
1
2
0
Order By: Relevance
“…The measured concentrations of Al are critical for the discussion, whereas Na, Fe, Mn, P and F are of secondary importance as only trace amounts are usually present (Table 5). Data obtained during our study and from the published papers of Novák and Filip (2010), Dolníček et al (2020) and Zachař et al (2020) revealed high variability in Al (and Be) and significant heterogeneity of some samples (Fig. 4).…”
Section: Resultssupporting
confidence: 57%
See 1 more Smart Citation
“…The measured concentrations of Al are critical for the discussion, whereas Na, Fe, Mn, P and F are of secondary importance as only trace amounts are usually present (Table 5). Data obtained during our study and from the published papers of Novák and Filip (2010), Dolníček et al (2020) and Zachař et al (2020) revealed high variability in Al (and Be) and significant heterogeneity of some samples (Fig. 4).…”
Section: Resultssupporting
confidence: 57%
“…3f) whereas textural relations of bavenite-bohseite with associated albite, muscovite and quartz on fractures are not clear. They are likely fragments of the fracture surface where late bavenite-bohseite crystallised (see also Dolníček et al, 2020); however, euhedral shape of quartz grains (see Fig. 3e) indicates that it recrystallised during or slightly before the formation of bavenite-bohseite.…”
Section: Textures and Mineral Assemblagesmentioning
confidence: 99%
“…The most fractionated pegmatites show an affinity to the LCT (lithium-caesium-tantalum) family and beryl–columbite subtype of the rare-element class according to the classification of Černý and Ercit (2005), as were documented by their mineral assemblages (e.g. Černý et al , 1992, 1995; Novák 1988, 2005; Novák et al , 2003, 2023; Chládek and Zimák, 2016; Chládek et al , 2020, 2021; Dolníček et al , 2020a, 2020b).…”
Section: Regional Geology and Pegmatite Descriptionmentioning
confidence: 98%